2011
DOI: 10.1510/icvts.2010.245225
|View full text |Cite
|
Sign up to set email alerts
|

Type A dissection in young patients

Abstract: Predominant etiologies for type A dissection in young patients are connective tissue diseases, BAV, severe hypertension, vascular diseases and cocaine abuse. Early in-hospital mortality rate was low and principally influenced by massive myocardial infarction due to coronary dissection as well as severe neurological disorders. Aortic root dilatation after a prosthetic ascending aortic replacement was the main re-operation cause and occurred earlier during follow-up than arch or more distal aortic dilatation. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…In our series, 13 patients (3.5%) were under 40 years old. Our findings were comparable to those of previous studies that found that patients with connective tissue disorders tended to present with AAAD at a younger age . Fourteen (27.5%) of 51 patients had connective tissue disorders, and the prevalence of connective tissue disorders increased with decreasing age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our series, 13 patients (3.5%) were under 40 years old. Our findings were comparable to those of previous studies that found that patients with connective tissue disorders tended to present with AAAD at a younger age . Fourteen (27.5%) of 51 patients had connective tissue disorders, and the prevalence of connective tissue disorders increased with decreasing age.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of patients with acute type A aortic dissection (AAAD) requiring surgical intervention are in their 60s and 70s . However, AAAD repair is sometimes necessary in younger patients . These patients are more likely than older patients to have a genetic component.…”
Section: Introductionmentioning
confidence: 99%
“…As this was not the case, it seems likely that other factors such as the presence of a bicuspid aortic valve and consecutively altered hemodynamics through the valve may well be a leading mechanism of aneurysm formation [11]. In acute type A aortic dissection one would expect a certain percentage of patients with connective tissue disease which was also not the case in this series [12,13]. These findings do further substantiate the need for accurate and early determination of patients being at risk for acute type A aortic dissection.…”
Section: Resultsmentioning
confidence: 98%
“…The rate of proximal reoperation was reported up to 50% at 10 years [28]. Similarly, young patients experienced a higher rate of proximal reoperation [29]. This problem should not be considered strictly in the light of the longer survival expectancy, the prolonged exposition to aortic complication or an easier acceptance for a redo procedure.…”
Section: Risk Factors Of Proximal Reoperation After Supracoronary Aormentioning
confidence: 99%